Significant others (Routledge (Firm))
1 online resource (257 p.)
Keywords: Significant Others explores the transformative possibilities of alterity or otherness and offers concrete case studies that provide a greater understanding and nuance with regard to aspects of deviance and difference in premodern court cultures. Both public and nominally private spaces were subject to the important influence of significant others, such as women, ethno-religious minorities, and marginalized and/or difficult-to-categorize men. From their positions within and ties to court cultures, these diverse outsiders- others' - played crucial roles in maintaining a fluidity essential for the successful sustaining of territorial monarchies and polities, challenging our understanding of the more narrowly defined elite behaviours that shaped premodern dynasties, rulers, societies, and cultures of the past. By exploring a variety of case studies from history and literature, such as Moroccan Jews as dhimmis (protected persons'), to bastards, mistresses, and sodomites in ancien rgime France, to the transformative role of magic in Sir Gawain and the Green Knight, this volume makes use of empirical and contextually informed research to respond to theoretical questions posed by recent historiography. With a cross-disciplinary approach, this collection of essays will be a valuable resource for all students and scholars interested in the diverse aspects and contexts of premodern others'.